2017
DOI: 10.1093/pch/pxx051
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour in-house neonatologist coverage and long-term neurodevelopmental outcomes of preterm infants

Abstract: Duration of mechanical ventilation was reduced with 24-hour in-house coverage by staff neonatologists. However, 24-hour coverage was not associated with any difference in neurodevelopmental (ND) outcomes at 3-year corrected age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Resnick and colleagues retrospectively studied 480 infants born at less than 32 weeks of gestational age before and after adopting an after-hours in-house senior physician cover and reported no major differences in neonatal outcomes [7]. Lodha and colleagues retrospectively studied 387 preterm infants before and after the introduction of a 24 h in-house staff neonatologist cover and reported no significant difference in neurodevelopmental outcomes at three years corrected age [8]. Our differing results of better outcomes following the introduction of resident consultants might be explained by population differences as we conducted a larger study and included all infants, rather than only those born prematurely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resnick and colleagues retrospectively studied 480 infants born at less than 32 weeks of gestational age before and after adopting an after-hours in-house senior physician cover and reported no major differences in neonatal outcomes [7]. Lodha and colleagues retrospectively studied 387 preterm infants before and after the introduction of a 24 h in-house staff neonatologist cover and reported no significant difference in neurodevelopmental outcomes at three years corrected age [8]. Our differing results of better outcomes following the introduction of resident consultants might be explained by population differences as we conducted a larger study and included all infants, rather than only those born prematurely.…”
Section: Discussionmentioning
confidence: 99%
“…Although, these recommendations have been in place for a number of years and in the recent years some units in the United Kingdom have introduced resident consultant cover, the effect of this intervention on neonatal outcomes has not been evaluated in the UK [6]. Studies from Australia [7] and Canada [8] have reported no significant differences in neonatal or neurodevelopment outcomes at three years of age, but the studies were relatively small and their results might not be directly applicable to a different health system.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report by Lodha et al [36] concluded in-house neonatologist coverage was associated with a reduction in the duration of mechanical ventilation in extremely preterm neonates. However, there was no difference in long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Jensen and Lorch [17] concluded that very low birth weight neonates born between midnight and 7: 00 a.m. are at higher risk for severe intraventricular hemorrhage and death or major neonatal morbidities. Lodha et al [18] concluded that there was no significant difference in neurodevelopmental outcomes at 3 years corrected age following 24 h a day in-house coverage by a staff neonatologist; however, it was associated with a reduction in the duration of mechanical ventilation in extremely preterm neonates. Resnick et al [19] reported that an after-hours in-house consultant neonatologist or neonatal fellow in the NICU until 11 p.m. showed no difference in outcomes of neonates < 32 weeks' gestation.…”
Section: Discussionmentioning
confidence: 99%